Site Visit vs Mental Visualization on Lanna Architecture: A Study on Working Memory in Young Adult - Tawipas Pichaichanarong (Graduate School of Institut Seni Indonesia Yogyakarta, 2021)
The rise of modern architecture styles has strongly impacted the younger generation globally in the current century. This research is designed to study the performance of working memory on understanding Lanna architecture with young adults at a large university in northern Thailand, that of Mae Fah Luang University in Chiang Rai Province, Thailand. In this study, the research focuses on studying the effectiveness of young adults’ working memory to discern Lanna architecture through site visits and mental visualization. The outcomes of this research can help improve architecture pedagogy in the future. For the methodology, questionnaires were used by collecting data from 412 university students from a university in northern Thailand. The data then were analyzed using mean, standard deviation, and p-value. This study concludes that the performance of working memory on the comprehension of Lanna architecture through site visits and mental visualization for young adults was positive. Kunjungan Situs vs Visualisasi Mental pada Arsitektur Lanna: Studi tentang Memori Kerja pada Anak Muda Abstrak Kemunculan gaya arsitektur modern memberi pengaruh kuat pada generasi muda di penjuru duina pada abad ini. Penelitian ini dirancang untuk mempelajari kinerja Memori kerja saat memahami arsitektur Lanna di kalangan anak muda pada sebuah universitas besar di Thailand utara, yaitu Universitas Mae Fah Luang di Provinsi Chiang Rai, Thailand. Dalam studi ini, penelitian berfokus pada bagaimana mempelajari efektivitas memori kerja anak muda untuk membedakan arsitektur Lanna melalui kunjungan situs dan visualisasi mental. Hasil dari penelitian ini dapat membantu meningkatkan pedagogi arsitektur di masa depan. Untuk metodologinya, kuesioner dikumpulkan dari 412 mahasiswa dari sebuah universitas di Thailand utara. Data kemudian dianalisis melalui rata-rata, standar deviasi, dan p-value. Penelitian ini menyimpulkan bahwa kinerja Memori kerja pada pemahaman arsitektur Lanna melalui kunjungan situs dan visualisasi mental pada anak muda memberi hasil yang positif.